Pengaruh Aplikasi Pupuk NPK Terhadap Pertumbuhan dan Produksi Tanaman Cabai Rawit (Capsicum frutescens L.) - Laia, Nova`ahakhododo; Harahap, Rahmaniah; Jabat, Yelfi Yana Linda Br (UNIVERSITAS LABUHANBATU, 2024)
Cayenne pepper or small chili (Capsicum frutescens L.) is an important horticultural crop in Indonesia which is most widely consumed by the community so that chili production has a very high potential and economic value for farmers also affects high economic value and is useful as a flavoring dish. This cayenne pepper plant is easy to grow in the lowlands and highlands and contains nutrients needed by the human body. Chili is a vegetable commodity that is not wasteful of land because it is more concerned with its cultivation technology to be improved so that production increases. Intensive cultivation and care of chili peppers and further using post-harvest technology creates new jobs. Some of the vitamin content contained in chili peppers includes vitamin C antioxidants that can prevent several diseases such as cancer and vitamin B which can improve digestion, help increase immunity and avoid the body from bacterial disease. One way to increase the yield of cayenne pepper plants is to increase soil productivity, using the addition of NPK fertilizer. This study used a factorial randomized group design (RAK). For accuracy in this study, it was repeated 3 times. namely: NPK fertilizer (N) with 3 levels, namely: N0 = Control, N1 = 15 g/plant, and N2 = 20 g/plant. From the ANOVA test results, the variance of treatments that have a significant effect is continued with the Duncan DMRT test at the 5% level. The results of the ANOVA test showed that the effect of NPK fertilizer treatment on plant height 2 weeks and 3 weeks, stem diameter (mm) 1 week, 2 weeks, and 3 weeks, and the number of flowers showed a significant effect. While the observation of plant height at 1 st, number of flowers, number of fruits per sample plant (g), and weight of fruits per sample plant showed no significant effect. The best average NPK fertilizer treatment is the treatment level N2 = 20 g/plant. Keywords: NPK fertilizer, NPK dosage, and cayenne pepper plants